2009
DOI: 10.1111/j.1523-5378.2009.00684.x
|View full text |Cite
|
Sign up to set email alerts
|

Distinct cagA EPIYA Motifs are Associated with Ethnic Diversity in Malaysia and Singapore

Abstract: Although, H. pylori strains with distinct cagA-types are circulating within the primary ethnic groups resident in Malaysia and Singapore, these genotypes appear unassociated with the development of GC in the ethnic Chinese population. The phenomenon of distinct strains circulating within different ethnic groups, in combination with host and certain environmental factors, may help to explain the rates of GC development in Malaysia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
27
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 55 publications
6
27
1
Order By: Relevance
“…This result in the current study is in accordance to another study by Schmidt et al 20 showing significantly more Chinese isolates encoding the EPIYA-D motif. Besides the EPIYA motif, another study by Schmidt et al 21 has also shown significant variation of the prevalence of dupa and HP0521 allele with ethnicity.…”
Section: Discussionsupporting
confidence: 96%
“…This result in the current study is in accordance to another study by Schmidt et al 20 showing significantly more Chinese isolates encoding the EPIYA-D motif. Besides the EPIYA motif, another study by Schmidt et al 21 has also shown significant variation of the prevalence of dupa and HP0521 allele with ethnicity.…”
Section: Discussionsupporting
confidence: 96%
“…It has been reported that in multiethnic societies, the distribution of cagA genotypes is not similar among different ethnic groups. For example, in Thailand, Malaysia, and Singapore, Eastern CagA is predominant among isolates from Chinese groups while Western CagA is predominant among isolates from Thais, Indians, and Malays (13,20,21,24). However, our method also has some disadvantages.…”
Section: Discussionmentioning
confidence: 91%
“…Such regions are found mostly in East Asia, including Okinawa, Thailand, Malaysia, and Singapore. (13,20,21,24). It has been reported that in multiethnic societies, the distribution of cagA genotypes is not similar among different ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, H. pylori strains carrying East Asian CagA (ABD-type CagA) are more closely associated with severe gastric atrophy and gastric carcinoma than are H. pylori strains carrying Western CagA (ABCn-type CagA) (29,30). Among H. pylori strains carrying Western CagA, those having CagA with a larger number of EPIYA-C segments are more likely to induce intestinal metaplasia and gastric carcinoma than are those having CagA with fewer EPIYA-C segments (31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%